Communicating inflation uncertainty and household expectations - Olena Kostyshyna; Luba Petersen (Bank of Canada, 2023)
This paper examines the value of direct communication to households about inflation and the uncertainty around inflation statistics. All types of information about inflation are effective at immediately managing inflation expectations, with information about outlooks being more effective and more relevant than that about recent inflation and Bank targets. We observe no downside to communicating about inflation with uncertainty on two measures: the level of expected inflation and uncertainty about it. On a third measure-probabilistic inflation expectations-we observe positive effects: they become more centered around the communicated ranges. However, communication with uncertainty weakens the link between expected inflation and spending plans, a key channel in the transmission of monetary policy. Communicating precise inflation outlooks can lengthen the effects of these communications on households.
Keywords: C93; D84; E59; E7; 330; Central Bank Research; Credibility; Inflation and prices; Inflation targets; Monetary policy and uncertainty; Monetary policy communications